2013
DOI: 10.1002/pmic.201200563
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of reproducibility in depletion and enrichment workflows for plasma proteomics using label‐free quantitative data‐independent LCMS

Abstract: Quantitation in plasma-based proteomics necessitates the reproducible removal of highly abundant proteins to enable the less abundant proteins to be visible to the mass spectrometer. We have evaluated immunodepletion (proteoprep20) and enrichment (Bio-Rad beads), as the current predominant approaches. Label-free analysis offers an opportunity to estimate the effectiveness of this approach without incorporating chemical labels. Human plasma samples were used to quantitatively assess the reproducibility of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
22
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 52 publications
(37 reference statements)
2
22
0
Order By: Relevance
“…A previous experiment by Bortner et al [19] performed by the same institutional Proteomic Mass Spectrometry core laboratory, which utilized a similar amount of starting material, prefractionization procedure and instruments, and the same mass spectrometer, verified two smoking-associated biomarker (ITI-HC3 and VDBP) in plasma of smokers after depletion of 20 highly abundant plasma proteins. In this study we implemented a proteins enrichment method, ProteoMiner (BioRad), which can enhance the depth of the proteomic analysis [35,36]. We were able to positively identify almost 2-fold more proteins than Bortner et al using the same quality control parameters (201 and 131, respectively), which suggested that protein enrichment may enhance the depth of proteomics analysis.…”
Section: Discussionmentioning
confidence: 86%
“…A previous experiment by Bortner et al [19] performed by the same institutional Proteomic Mass Spectrometry core laboratory, which utilized a similar amount of starting material, prefractionization procedure and instruments, and the same mass spectrometer, verified two smoking-associated biomarker (ITI-HC3 and VDBP) in plasma of smokers after depletion of 20 highly abundant plasma proteins. In this study we implemented a proteins enrichment method, ProteoMiner (BioRad), which can enhance the depth of the proteomic analysis [35,36]. We were able to positively identify almost 2-fold more proteins than Bortner et al using the same quality control parameters (201 and 131, respectively), which suggested that protein enrichment may enhance the depth of proteomics analysis.…”
Section: Discussionmentioning
confidence: 86%
“…About 95% of the proteome is composed of 10–12 proteins, which can interfere with MS-based approaches for identifying and quantifying less abundant proteins. The removal of albumin and other highly abundant proteins via antibody depletion has become standard practice [3,25]. Recently the immunodepletion of abundant blood-derived proteins from solid tissue specimens has been recommended [29].…”
Section: Discussionmentioning
confidence: 99%
“…The challenges associated with plasma proteomics include the large dynamic range of protein concentrations [1,2], variability in preanalytic and analytic processes, and inherent biological variability. Detection of low abundance proteins is facilitated by depletion or enrichment of peptides or proteins prior to mass spectrometry (MS) analyses [3]. The use of sound study designs and system suitability protocols improves analytical reproducibility and statistical power [47].…”
mentioning
confidence: 99%
“…To date, MS coupled with highresolution liquid chromatography (LC) has been the preferred tool for the identification of trypsin-digested N-glycopeptides and glycosylation sites (7,8). However, study of the human plasma glycoproteome remains challenging because of the vast dynamic range of protein abundance, which can span up to 12 orders of magnitude (8).…”
mentioning
confidence: 99%
“…To date, MS coupled with highresolution liquid chromatography (LC) has been the preferred tool for the identification of trypsin-digested N-glycopeptides and glycosylation sites (7,8). However, study of the human plasma glycoproteome remains challenging because of the vast dynamic range of protein abundance, which can span up to 12 orders of magnitude (8). In addition, the low ionization efficiency of plasma glycopeptides, combined with the relatively high quantities of interfering nonglycosylated counterparts in the sample, can often result in signal suppression when subjected to MS analyses (7).…”
mentioning
confidence: 99%